Russia’s Invasion of Ukraine and its Impact on Global Geopolitics - Tampubolon, Manotar (European Scientific Journal, ESJ, 2022)
On February 24, 2022, Russia attacked Ukraine. Here as consequence, Russia was subjected to a slew of international sanctions aimed at pressuring it to de-escalate the issue. Even though the economic sanctions issued against Russia were designed to harm this country, all of them had unintended consequences on the economic system of the world, essentially due to global supply chains disruptions. Power, commodities, as well as commerce flow disruptions emerged from the military attacks. Such issue resulted in energy costs got much higher, commodity prices, as well as food prices, all of which contributed to greater inflation on a worldwide scale in several nations. Despite the fact that many attempts of negotiation were created in resolving the conflict between Ukraine and Russia, its political, social, and economic impacts lasted in numerous countries of Europe and other regions around the world.